Organizing Training Sessions For Submitting Health Test Requirements And Standards (Texas Journal of Medical Science, 2025)
In this article, health tests are used to determine the physical development and physical fitness of the population, and to form a habit of systematically performing physical exercises for a healthy lifestyle.